Overpayment to employee by mistake: Recovery through salary deduction - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (LexisNexis Malaysia Sdn Bhd, 2017)
In the sphere of employment law, in the absence of a statutory provision enabling an employer to make deduction for overpayment by mistake or a 'deduction clause' in the employment contract, there is no automatic mechanism that allows the employer to recover an overpayment through deduction of the amount from the employees next pay A 'deduction clause' simply means that the employee consents to the employer making deductions from the employee's future wages or salary. With the consent of the employee, the employer may make an arrangement for the employee to repay the overpaid sum by a series of deductions from his salary each month until all money due had been repaid. What if the employee had altered or changed his position in reliance on those overpayments, whether the employer may still pursue to recover the overpaid money and if so, whether it could be done unilaterally by the employer or a court order is necessary. Hence, this article discusses the right of an employer to recover the overpayment of salary or wages by mistake.